ANALISIS PENAWARAN DAN PERMINTAAN BBM (Studi Kasus di Propinsi Daerah Istimewa Yogyakarta) - Ahmad Ma'ruf (Jurnal Ekonomi & Studi Pembangunan, 2005)
Fuel oil or bahan bakar minyak (BBM) is among the most strategic commodity in Indonesia. Any change either in its price, quantity or both will immediately affect the macro as well as microeconomic stability. Therefore, maintaining synchronization in the supply of BBM and demand for it is necessary, in order to ensure the social welfare improvement and macroeconomic stability of the community. It is remarkably admitted that market structure of the BBM until 2004 has been monopolistic, which directly implies to the pattern of the BBM supply. As BBM becomes the primary commodity in the community, especially in industrial sector and transportation, the demand for B BM is consequently inelastic. The inelastic demand for BBM is applied to its main types such as gasoline, diesel, kerosene, and elpiji (natural gas), though the degree may vary from one to a not her.